The use of psychological skills by female collegiate swimmers - Huddleston, S.; Thiese, K. (Journal of Sport Behavior, 1999)
Female collegiate swimmers (N = 147) from 10 mid-western university teams completed a questionnaire concerning the use of mental skills. Ss were divided into sprint and long distance performers. Goal-setting (66.7%), self-talk (40.1%), and music for psyche-up (27.9%) were the most frequently indicated skills. Of lesser frequency were focusing internally, imagery/visualization, and music for relaxation. Activities rarely reported as being used included autohypnosis, autogenic training, blank meditation, bracing, color, cue words, mantra meditation, and Transcendental Meditation. The types of mental skills used were similar between sprint and long-distance swimmers. Implication: Female collegiate swimmers reported a low use of mental skills.